2021
DOI: 10.1177/00333549211061313
|View full text |Cite
|
Sign up to set email alerts
|

Disaggregating Asian Race Reveals COVID-19 Disparities Among Asian American Patients at New York City’s Public Hospital System

Abstract: Objectives: Data on the health burden of COVID-19 among Asian American people of various ethnic subgroups remain limited. We examined COVID-19 outcomes of people of various Asian ethnic subgroups and other racial and ethnic groups in an urban safety net hospital system. Methods: We conducted a retrospective analysis of 85 328 adults aged ≥18 tested for COVID-19 at New York City’s public hospital system from March 1 through May 31, 2020. We examined COVID-19 positivity, hospitalization, and mortality, as well a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 29 publications
(28 reference statements)
0
22
0
Order By: Relevance
“…This study reported that while rates of COVID‐19 positivity, hospitalization, and mortality were lower among the overall Asian group, disaggregating Asians into their ethnic subgroups revealed a very different picture. Chinese patients had a higher mortality rate (35.7%) than South Asian (23.7%) and other Asian (21.0%) patients, and this rate was the highest among all racial and ethnic groups (Kalyanaraman Marcello et al, 2022).…”
Section: The “Model Minority” Mythmentioning
confidence: 98%
See 2 more Smart Citations
“…This study reported that while rates of COVID‐19 positivity, hospitalization, and mortality were lower among the overall Asian group, disaggregating Asians into their ethnic subgroups revealed a very different picture. Chinese patients had a higher mortality rate (35.7%) than South Asian (23.7%) and other Asian (21.0%) patients, and this rate was the highest among all racial and ethnic groups (Kalyanaraman Marcello et al, 2022).…”
Section: The “Model Minority” Mythmentioning
confidence: 98%
“…Empirical data, though limited, also show differences in outcomes between different Asian ethnic subgroups of people. One study in New York City, which had high morbidity and mortality rates during the COVID-19 pandemic, disaggregated Asian subgroups to understand the burden faced within the Asian community as it relates to infections and hospitalizations (Kalyanaraman Marcello et al, 2022).…”
Section: The " Model Minority" Mythmentioning
confidence: 99%
See 1 more Smart Citation
“… 15 Estimates indicated a high burden of COVID-19 deaths among Asian Americans, with almost 14,000 excess deaths; Asian Americans have the second-highest increase in deaths following Hispanic Americans, using data from July of 2020. 16 Similarly, high rates of COVID-19 infection, hospitalization, and mortality among South Asian and Chinese American adults have been reported, 17 highlighting the heterogeneous health outcomes within the “Asian American” umbrella category.…”
Section: Covid-19-related Health Disparities Among Asian Americansmentioning
confidence: 99%
“…While limited research has uncovered disparities in COVID-19 mortality outcomes among specific Asian subgroups in specific geographic regions and contexts, such as Hmongs in Minnesota [30], Chinese and South Asians in New York City [31], and Filipinos in California [32], little to no attention by national media outlets and public health officials has been given to vulnerable Asian subgroups [33]. To date, there has not been a national-level analysis of COVID-19 mortality outcomes between Asian subgroups in the U.S. To this end, I utilized final multiple cause of death data for 2020 that were released in December 2021 and population projections from the U.S. Census Bureau’s Current Population Survey Annual Social and Economic Supplement ASEC for 2020 to calculate crude, age-adjusted, and sex-stratified national COVID-19 mortality rates for the six major Asian origin subgroups (Asian Indians, Chinese, Filipino, Japanese, Korean, Vietnamese), as well as a catch-all seventh category that comprises the remaining less-populous Asian subgroups (Other Asians), contrasting them with the corresponding mortality rates of other racial/ethnic groups.…”
Section: Introductionmentioning
confidence: 99%